2021
DOI: 10.3390/cancers13112802
|View full text |Cite
|
Sign up to set email alerts
|

Interfractional Geometric Variations and Dosimetric Benefits of Stereotactic MRI Guided Online Adaptive Radiotherapy (SMART) of Prostate Bed after Radical Prostatectomy: Post-Hoc Analysis of a Phase II Trial

Abstract: Purpose: To evaluate geometric variations of patients receiving stereotactic body radiotherapy (SBRT) after radical prostatectomy and the dosimetric benefits of stereotactic MRI guided adaptive radiotherapy (SMART) to compensate for these variations. Materials/Methods: The CTV and OAR were contoured on 55 MRI setup scans of 11 patients treated with an MR-LINAC and enrolled in a phase II trial of post-prostatectomy SBRT. All patients followed institutional bladder and rectum preparation protocols and received f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 28 publications
1
7
0
Order By: Relevance
“…Changes in the positioning of internal organs between fractions can also be assessed with MRgRT and trigger adaptation of the predicted plan (plan with new MR image and edited structures but original plan dose). Similar dosimetric benefits have been observed in multiple sites using adaptation to account for interfractional motion [ 80 , 81 , 82 ].…”
Section: Current Mrgrt Systems and Applicationssupporting
confidence: 62%
“…Changes in the positioning of internal organs between fractions can also be assessed with MRgRT and trigger adaptation of the predicted plan (plan with new MR image and edited structures but original plan dose). Similar dosimetric benefits have been observed in multiple sites using adaptation to account for interfractional motion [ 80 , 81 , 82 ].…”
Section: Current Mrgrt Systems and Applicationssupporting
confidence: 62%
“…To date, the inefficient nature of MRI-guided online adaptive radiation therapy has been limited in our department to cases where the benefits of daily replanning are expected to be high (i.e., stereotactic body radiation therapy, hypofractionated radiation therapy, and reirradiation). The benefits online adaptive therapy can provide for short-course therapy have been well described, particularly for SBRT of the prostate [ 14 , 15 , 16 ]. This study provides the blueprint for a physician-free, real-time on-table adaptive radiotherapy (PF-ROAR) through the expansion of roles of certain members of the clinical team while maintaining daily adaptive plan quality for carefully selected patients.…”
Section: Discussionmentioning
confidence: 99%
“…A CTV V95% was greater than 93% for 13/18 patients. In patients receiving post-prostatectomy SBRT in a single institution phase II trial, Cao et al use MRI-guided adaptive RT to account for variations in CTV and OARs [35]. They reported the stability of CTV volume and shape with a 3.0% median volume change.…”
Section: Discussionmentioning
confidence: 99%
“…They reported the stability of CTV volume and shape with a 3.0% median volume change. MRI-guided adaptive therapy was deemed to be beneficial in approximately 78.2% of the 55 fractions due to target under-coverage, exceeding OAR constraints, or both [35]. In their initial report of a phase III trial evaluating MRI image-guided SBRT versus CT-guided SBRT for intact prostate cancer, Kishan et al demonstrated that acute grade >2 GU toxicity was reduced in patients who received MRI-guided SBRT [36].…”
Section: Discussionmentioning
confidence: 99%